Study Experimental of Diesel Engines Performance by Using Variations of Mesh Filter and Biodiesel B40, B50 as Fuel - Romy Romy; Zuchra Helwani; Asal Felix Mandrofa (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2022)
Biodiesel is an alternative fuel, which can be used as a substitute for fossil fuels. Biodiesel has different characteristics than fossil fuels, so need study to improve engine performance. One way to improve engine performance by vary the fuel filter mesh. In this study by varied the size of the filter mesh with sizes of 2, 10, and 30 microns. This study used B40 (a ratio 60% diesel and 40% biodiesel) and B50 (a ratio 50% diesel and 50% biodiesel) as fuel. Then, an engine rpm was varied by brake pressure load of 2500 kg/m2, 5000 kg/m2, 7500 kg/m2, 10000 kg/m2, and 12500 kg/m2. As results, the optimal mesh size used for B40 was 2 microns and 30 microns for B50 fuel. From the comparison of engine performance results, the fuel filter mesh used in B40 fuel has better engine performance results compared to B50.